Diabetic nephropathy and its risk factors among patients with diabetes mellitus-an observational study - Sumanta Kumer Saha; M. D. Mohammad Saifuddin; Tamanna Tabassum Moni; M. Rezaul Kadir; Aliva Haque; Sabiha Tabassum Mithila (International Journal of Research in Medical Sciences, 2023)
Background: Diabetic nephropathy (DN) is frequently associated with T2DM and the leading cause of chronic kidney disease and end-stage renal disease. Diabetic nephropathy is one of the three classic micro-vascular complications of diabetes mellitus (DM), traditionally described among patients with long duration and poor control of DM. The aim of this study was to identify and evaluate the risk factors for diabetic nephropathy among patients with DM. Methods: This was a retrospective observational study and was conducted in the department of medicine, LABAID specialized hospital, Dhaka, Bangladesh during the period from March 2022 to March 2023. We included 345 patients with DM and diabetic nephropathy in our study. Results: In our study the mean age was 43.1±9.3 years and majority (57%) of patients were female. Among all patients 48% had diabetes for less than 8 years. Majority (72%) patients got nephropathy because of elevated glucose levels. We found other risk factors like advanced age (37.39%), smoking (27.83%), obesity (61.16%), elevated blood pressure (53.33%), dyslipidemia (20%), longer duration of diabetes (47.25%), family history of DM and DN (21.45% and 24.35%) and retinopathy (25.80%). Conclusions: In our study, we found advanced age, high glucose level, high blood pressure, obesity, long duration of DM, family history of DM and diabetic nephropathy, smoking, dyslipidemia and concomitant diabetic retinopathy were significant risk factors for diabetic nephropathy among selected diagnosed diabetic patients.